2003
DOI: 10.1002/cnm.645
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the Laplace inverse transform by application of the wavelet theory

Abstract: SUMMARYAn e cient and robust method of solving Laplace inverse transform is proposed based on the wavelet theory. The inverse function is expressed as a wavelet expansion with rapid convergence. Several examples are provided to demonstrate the methodology. As an example of application, the proposed inversion method is applied to the dynamic analysis of a single-degree-of-freedom spring-mass-damper system whose damping is described by a stress-strain relation containing fractional derivatives. The results are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 16 publications
(26 reference statements)
0
60
0
Order By: Relevance
“…[9], according to Eqs. [6] and [7], we have h͑T͒ ϭ P͑␣͒, [10] which means that the distribution of scaled relaxation times T is proportional to the distribution of pore sizes ␣. In this particular case, the relaxation time, and not the relaxation rate, is proportional to the physical heterogeneity parameter.…”
Section: Nmr Of Heterogeneous Systemsmentioning
confidence: 99%
“…[9], according to Eqs. [6] and [7], we have h͑T͒ ϭ P͑␣͒, [10] which means that the distribution of scaled relaxation times T is proportional to the distribution of pore sizes ␣. In this particular case, the relaxation time, and not the relaxation rate, is proportional to the physical heterogeneity parameter.…”
Section: Nmr Of Heterogeneous Systemsmentioning
confidence: 99%
“…For simplicity, we specify [1], it can be shown that = 7 in the case of N = 6. Using this approximation of , Equation (1) can be simpliÿed as…”
Section: A Simple Formula Of Laplace Inversionmentioning
confidence: 99%
“…By applying wavelet theory, we have previously suggested an inversion formula of Laplace transform as [1] …”
Section: A Simple Formula Of Laplace Inversionmentioning
confidence: 99%
See 2 more Smart Citations